The global challenge of encouraging sustainable living : opportunities, barriers, policy and practice - Fudge, Shane; Peters, Michael D. (Michael Derek), 1975-; Hoffman, Steven M.; Wehrmeyer, Walter (Cheltenham, UK : Edward Elgar, 2013)
This book illustrates that in order to address the growing urgency of issues around environmental and resource limits, it is clear that we need to develop effective policies to promote durable changes in behavior and transform how we view, and consume, goods and services. It suggests that in order to develop effective policies in this area, it is necessary to move beyond a narrow understanding of'how individuals behave', and to incorporate a more nuanced approach that encompasses behavioral influences in different societies, contexts and settings. The editors draw together analyses and case studies from across the globe and from multi-disciplinary perspectives in order to offer a broad-based psychological, sociological and economic understanding of consumer behavior. The expert contributors, from both academic and practitioner backgrounds discuss in detail the barriers, challenges and opportunities that face governments in relation to policy and actions at local, national and supranational levels.
The psychology of behaviour change : an overview of theoretical and practical contributions / Wokje Abrahamse and Judith de Groot -- Peak electricity demand and social practice theories : reframing the role of change agents in the energy sector / Yolande Strengers -- Economic and non-economic factors driving household expenditure : methodological reflections on an econometric analysis / Scott Milne -- Scenarios as tools for initiating behaviour change in food consumption / Andrea Farsang and Lucia Reisch -- Emergent futures? Signposts to sustainable living in Europe and pathways to scale / Cheryl Hicks and Michael Kuhndt -- Identifying relevance and strength of barriers to changes in energy behaviour among end consumers and households : the BarEnergy project / Martin van de Lindt, Sophie Emmert and Helma Luiten -- Collaborative (and sustainable) behaviours : grassroots innovation, social change and enabling strategies / Ezio Manzini -- From energy policies to energy-related practices in France : the figure of the'consumer citizen' as a normative compromise / Mathieu Brugidou and Isabelle Garabuau-Moussaoui -- Decoupling environmental impact from economic growth in Norway : viable policy or techo-optimistic [sic] fantasy? / P{uA86C} Strandbakken and Eivind St{u0B6D} Living smart in Australian households : sustainability coaching as an effective large-scale behaviour change strategy / Colin Ashton-Graham and Peter Newman -- Energy demand implications of structural changes in India / Subhes C. Bhattacharyya -- Institutions and community-based initiatives in energy planning / Steven M. Hoffman and Angela High-Pippert.
Includes bibliographical references and index.
Keywords: Sustainable living -- Case studies; Sustainable living -- Government policy -- Case studies; Sustainability -- Case studies; Sustainability -- Government policy -- Case studies; Consumer behavior -- Case studies